JSE 31:1 Editorial - Braude, Stephen (Journal of Scientific Exploration, 2017)
In my view, the time is long overdue to remind—or just as likely, to inform—readers about the Hypothesis of Trans-Temporal Inhibition, advanced by Charles Tart in the 1970s to account for some striking features of data obtained in several of his ESP studies. Although in these studies Tart was exploring the importance of immediate feedback, the real interest of his results lies not so much in the strength of their evidence for ESP—at least as determined by the customary measures of deviation of hits from mean chance expectation.1 It concerns, rather, a certain unexpected pattern in the data, quite unlike familiar position or decline effects. This pattern suggests not only a new way of measuring the presence of ESP effects in data, but also some new ways of conceptualizing psi functioning. Tart’s analysis is quite complicated, and my own brief summary will hardly do justice to the care with which he interpreted his results. But I’ll try to indicate in broad terms what Tart had in mind, and I encourage interested readers to go to the source for the full story (see Tart, 1977a, 1977b, 1983), and also Tart’s more recent thoughts on the subject elsewhere in this issue. To understand Tart’s hypothesis, we must first review a particular approach to analyzing ESP data. Parapsychologists frequently look for evidence of time-displacement in ESP scores, because they’ve realized for some time that, while percipients’ calls at t may not correspond significantly to targets generated at t, they may correspond significantly to targets generated before or after t. For instance, we may obtain no above-chance scores when comparing calls at ti with targets generated at ti. But above-chance scores may result from comparing calls at ti with (say) the (ti + 1)th target. That sort of consistent scoring may be taken as evidence for precognitive ESP.